2016
DOI: 10.1073/pnas.1604773113
|View full text |Cite
|
Sign up to set email alerts
|

Parent-of-origin effects of A1CF and AGO2 on testicular germ-cell tumors, testicular abnormalities, and fertilization bias

Abstract: Testicular tumors, the most common cancer in young men, arise from abnormalities in germ cells during fetal development. Unconventional inheritance for testicular germ cell tumor (TGCT) risk both in humans and mice implicates epigenetic mechanisms. Apolipoprotein B mRNA-editing enzyme complex 1 (APOBEC1) cytidine deaminase and Deadend-1, which are involved in C-to-U RNA editing and microRNA-dependent mRNA silencing, respectively, are potent epigenetic modifiers of TGCT susceptibility in the genetically predisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 137 publications
(192 reference statements)
1
24
0
Order By: Relevance
“…Firstly, the embryonic lethality reported for A1cf tm1Ddsn occurs early in gestation, between E3.5 and E7.5, and prior to the reported onset of A1cf expression (Blanc et al 2005). Secondly, a recent report demonstrated that the A1cf tm1Ddsn allele displays a transmission distortion ratio (Carouge et al 2016), which is often indicative of chromosomal rearrangements such as Robertsonian translocations (Underkoffler et al 2005). Taken together, this evidence suggests the A1cf tm1Ddsn allele phenotype may be a result of additional, unintended genetic alterations unrelated to the loss of A1CF.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the embryonic lethality reported for A1cf tm1Ddsn occurs early in gestation, between E3.5 and E7.5, and prior to the reported onset of A1cf expression (Blanc et al 2005). Secondly, a recent report demonstrated that the A1cf tm1Ddsn allele displays a transmission distortion ratio (Carouge et al 2016), which is often indicative of chromosomal rearrangements such as Robertsonian translocations (Underkoffler et al 2005). Taken together, this evidence suggests the A1cf tm1Ddsn allele phenotype may be a result of additional, unintended genetic alterations unrelated to the loss of A1CF.…”
Section: Discussionmentioning
confidence: 99%
“…For Pum1, m/m embryos were not detected at E3.5 and litter size did not differ between intercrosses and backcrosses. 47 For A1cf, the heterozygote excess ranges from 3-to 5-fold, instead of the expected value of 2, based on two reports; 48,49 Loss of homozygous embryos between E3.5 -4.5 does not account for excess heterozygosity or for normal litter size. 48 Although litter size was not reported for Ppp2cb, 50 the highly significant heterozygote excess (>3:1) in intercrosses versus backcrosses is striking and consistent with results for A1cf, Ddx1 (see below) and Pum1.…”
Section: What Is the Evidence For Fertilization Bias?mentioning
confidence: 99%
“…[188][189][190] Various mechanisms preserve genomic integrity and developmental capacity of the 'mother of all stem cell lineages' 191 by repairing DNA defects, 192 maintaining cellular conditions, 193 suppressing transposon activity, [194][195][196][197][198][199] and programming epigenetic state. 200,201 Failure of pluripotency control can lead to precocious differentiation of germ cells, 202,203 spontaneous transformation of germ cells during fetal development, 142,185,186,204 , infertility, 49,205,206 and other reproductive disorders. 204 Dysfunction can also lead to inherited epigenetic changes that affect risk for TGCTs and urogenital abnormalities in offspring and later generations in the absence of genes that originally triggered these transgenerational effects.…”
Section: What Are the Mechanisms?mentioning
confidence: 99%
See 2 more Smart Citations